The correlation between antimicrobial resistance patterns and ESβL-encoding genes in gram-negative bacteria from patients with diabetic foot ulcers - Abdulghaffar, S. N.; Kadhim, H. I.; Saheb, E. J.; Al-Rubaey, N. K. F. (Regulatory Mechanisms in Biosystems, 2026)
Diabetic foot ulcer (DFU) is an important consequence of diabetes mellitus that may lead to serious infecte ion and lower-limb amputation. These infections are often polymicrobial, with increasing rates of multidrug resistance (MDR) from g ram-negative bacteria making treatment difficult. The present study aims to investigate gram-negative bacteria isolated from individuals with DFUs, their antibiotic resistance patterns, and confirm the presence of some important resistance genes using molecular techniques. This cross-sectional study comprised 280 individuals with infected diabetic foot ulcers. Bacterial isolates were obtained from swab and tissue specimens utilizing conventional microbiological tec h niques. The isolates were evaluated for the generation of ESβLs. Antimicrobial susceptibility was assessed using the disk diffusion technique (MIC). A PCR test was conducted to detect ESβL genes ( blaTEM , blaSHV , blaCTX-M ) in resistant strains. Out of 280 positive cultures, gram-negative bacteria accounted for 64.6% (n = 181) of infections. Among 117 selected major gram-negative isolates, 92 (78.6%) were ESβL producers. Phenotypically, E. coli 34 (37%), P. aeruginosa 31 (33.7%), and K. pneumoniae 27 (29.3%) were the dominant ESβL-positive species. Significant resistance was found against β-lactams, fluoroquinolones, and cephalosporins, whereas carbapenems, polymyxin B, and amikacin retained high efficacy. Molecular analysis revealed the blaCTX-M gene as the most prevalent (68.5%), followed by blaTEM (54.3%) and blaSHV (39.1%). Gram-negative bacteria were the main cause of DFUs, showing a h igh level of resistance to multiple drugs and a high number of ESBL-producing organisms. These results highlight the need for strict antibiotic stewardship and culture-directed therapy to enhance treatment outcomes and lower amputation risk.